EFICIÊNCIA DA ADUBAÇÃO FOSFATADA INFLUENCIADA PELA APLICAÇÃO DE GESSO AGRÍCOLA EM SISTEMA PLANTIO DIRETO - Galetto, Shivelly Los (2016)
The main objective of this work was to evaluate the efficiency of phosphate fertilization influenced by the application of agricultural gypsum for wheat and soybean crops under notillage system. For this, two experiments were carried out in the field and two in a greenhouse.The experiments in the field were installed in October 2013 in the municipality of Ponta Grossa – PR, in two Oxisols with different textural classes: a Red Oxisol (LV) clay texture and a Red-Yellow Oxisol (LVA) sandy-loam texture. The experimental design of the two soils was a randomized complete block in a split-plot, with three replications. In the plots,four rates of P (0, 30, 60 and 90 kg P2O5 ha-1) in the form of triple superphosphate (TSP) were applied at sowing and, in the subplots, four rates of agricultural gypsum (0, 2, 4 and 6 t ha-1),on the soil surface, before soybean sowing. In both soils, the immediate effects of treatments with P2O5 and gypsum in the soybean crop were evaluated. The effects of treatments on the succession of wheat (2014) – soybean (2014–15) were also evaluated in the clay Red Oxisol.In this case, in each crop (soybean and wheat), the same rates of P P2O5, in the form of TSP,were applied at the sowing, and the residual effect of the application of agricultural gypsum was evaluated. The experiments in greenhouse were carried out with wheat and soybean crops in undisturbed columns of soil. The PVC columns were taken from the Red Oxisol used in the field experiment. The experimental design used for each culture was in randomized blocks in a 3 × 2 factorial scheme, with four replications. The treatments were: control, agricultural gypsum and pure CaSO4.2H2O, without and with application of P2O5, in the form of TSP. The rate of agricultural gypsum and pure CaSO4.2H2O was corresponding to 6 t ha-1 and the rate of P was 90 kg ha-1 of P2O5. In all experiments, soil chemical attributes, plant attributes (nutrient extraction and dry mass production) and root attributes were evaluated. In the field experiments, nutritional diagnosis, nutrient exportation and grain yield of the crops were also evaluated. The P utilization efficiencies were calculated for wheat and soybean crops. In general, it was observed that, in the short term, gypsum did not influence P use efficiency (PUE) by soybean cultivated in RL and BL, but the residual effect of gypsum increased PUE by the rate of 5 t ha-1, and also the PUE of the soybean, up to the rate of 4.3 t ha-1. Adjusting the gypsum and P at sowing rates appropriately, it was possible to obtain high grain yields of wheat (above 4,5 t ha-1) and soybean (above 4 t ha-1) and provides economy of the phosphate fertilizer. However, it has been observed in all years that the highest rate of P at sowing (90 kg ha-1 of P2O5) associated with the highest rate of agricultural gypsum (6 t ha-1), in soils that had high levels of P, impaired root growth and wheat and soybean grain yields. In the experiments in greenhouse, it was verified that the application of pure CaSO4.2H2O and with 90 kg ha-1 of P2O5 at the sowing promoted improvement in the root system and in the production of wheat dry mass, and did not interfere in the soybean crop. These results have shown that the use of gypsum can increase PUE and improve the productive performance of wheat and soybean plants. However, the use of high rates of P at sowing associated with high rates of agricultural gypsum should be carried out with caution, especially in soils that already have adequate levels of available P, so that crop performance do not be impaired.